Non-reciprocal band structures in an exciton–polariton Floquet optical lattice - del Valle Inclan Redondo, Yago (2024)
Periodic temporal modulation of Hamiltonians can induce geometrical and topological phenomena in the dynamics of quantum states. Using the interference between two lasers, we demonstrate an off-resonant optical lattice for a polariton condensate with controllable potential depths and nearest-neighbour coupling strength. Temporal modulation is introduced via a gigahertz frequency detuning between pump lasers, creating a polariton ‘conveyor belt’. The breaking of time-reversal symmetry causes band structures to become non-reciprocal and acquire a universal tilt given by Planck’s constant and the frequency of modulation (hΔf). The non-reciprocal tilting is connected to the non-trivial topology of the Floquet–Bloch bands, which have a finite Chern number. Detailed characterization of the lattice potential depth and its dynamics highlights the role of high-energy carriers in the formation of optical potential landscapes for polaritons, demonstrating the possibility of modulation faster than the polariton lifetime and opening a pathway towards Floquet engineering in polariton condensates.